AN INTRODUCTION TO SOLAR CELL TECHNOLOGY - Ranabhat, Kiran; Patrikeev, Lev; Revina, Aleksandra Antal'evna; Andrianov, Kirill; Lapshinsky, Valerii; Sofronova, Elena (Journal of Applied Engineering Science, 2016)
Solar cells are a promising and potentially important technology. In this paper we are describing the fabrication, the development and the uses the different types of photovoltaic cells or solar cells. Today the consumption of energy is increasing every second but todays resources i.e. fossil fuel, which is limited, will be exhausted sooner or later, also global warming and pollution create acute problems due to its use. Today we need to think about the renewable and environment friendly source of energy to save the future society, this can be possible on the base of solar energy. We hope that ultimately solar energy can be extensively used in the commercial sector as well as the private sector. Imagine solar cells installed in cars to absorb solar energy to replace the traditional use of diesel and gas. People will vie to park their cars on the top level of parking garages so their cars can be charged under sunlight. Using the same principle, cell phones can also be charged by solar energy. There are such a wide variety of applications.